Experimental investigation of phase change amine solutions used in CO2 capture applications: Systems with dimethylcyclohexylamine (DMCA) and Ncyclohexyl-1, 3-propanediamine (CHAP) or 3-methylaminopropylamine (MAPA). (July 2021) - Tzirakis, Fragkiskos; Tsivintzelis, Ioannis; Papadopoulos, Athanasios I.; Seferlis, Panos
Highlights: Screening experiments for the CO2 loading of aqueous DMCA/MAPA and DMCA/CHAP systems. VLLE behavior was observed at various experimental conditions. Various solvent systems were evaluated in terms of CO2 absorption and cyclic capacity. Densities of liquid phases in equilibrium were measured. Abstract: Solvent-based absorption/desorption is a promising CO2 capture technology, but its wide industrial implementation is prohibited by the high energetic requirements incurred by conventional amine solvents. Such challenges can be addressed by phase-change solvents that have been shown to enable both lower energy consumption and capture costs. Despite their clear advantages, the limited availability of detailed phase equilibrium data hinders their consideration in scaling-up studies of phase-change CO2 capture processes. In this study, CO2 loading and phase compositions of novel phase change aqueous amine solutions are experimentally investigated. Phase equilibrium experiments are carried out to measure the CO2 loading of aqueous mixtures containing N, N -dimethylcyclohexylamine (DMCA) with 3-methylaminopropylamine (MAPA) and N, N -dimethylcyclohexylamine (DMCA) with N Cyclohexyl-1, 3-propanediamine (CHAP) at 40, 60 and 90 °C. It is observed that both systems exhibit phase change behavior, while DMCA-CHAP presents higher cyclic capacity and rather low volatility losses.